The effectiveness of a self-efficacy enhancement program on health behaviors and clinical outcomes in people with metabolic syndrome: A quasi-experimental study in Thailand - Madsong, Chalermkwan; Lininger, Jiraporn; Terathongkum, Sangthong (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Metabolic syndrome (MetS) is a cluster of chronic conditions, including obesity, hyperglycemia, hypertension, and dyslipidemia, known to significantly increase the risk of cardiovascular diseases (CVDs). Effective interventions are needed to control the progression of MetS. Objective: This study aimed to determine the effectiveness of the Self-Efficacy Enhancement (SEE) program on health behaviors and clinical outcomes in individuals with Metabolic Syndrome (MetS). Methods: A quasi-experimental study with a two-group pretest-posttest design was conducted from September 2023 to January 2024. A purposive sample of 70 participants with MetS was recruited from two healthcare settings in Thailand. Participants were divided into two groups: an experimental group (n = 35) and a control group (n = 35). The experimental group received the SEE program based on Self-Efficacy Theory, while the control group received only routine nursing care for 12 weeks. Data were collected using a Personal Information questionnaire, a Health Behavior questionnaire, and clinical outcome assessments, including waist circumference (WC), blood pressure (BP), fasting plasma glucose (FPG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL cholesterol), and non-high-density lipoprotein cholesterol (non-HDL cholesterol), before and after the 12-week program. Data were analyzed using descriptive statistics, paired t-test, independent t-test, Wilcoxon signed-rank test, Mann-Whitney U-test, and ANCOVA. Results: Following the SEE program, the experimental group exhibited significant improvements in health behaviors (t = -12.830, p <0.001), a reduction in WC (t = 3.809, p <0.001), decreased SBP (z = -4.554, p <0.001) and DBP (t = -5.178, p <0.001), and an increase in HDL cholesterol (z= -3.193, p <0.001) compared to baseline measures. Furthermore, compared to the control group, the experimental group demonstrated significantly improved health behaviors (F = 193.86, p <0.001), lower WC (F = 19.58, p <0.001), lower FPG (F = 12.39, p <0.001), lower SBP (F = 25.04, p <0.001), lower DBP (F = 19.49, p <0.001), and lower non-HDL cholesterol (F = 8.49, p <0.01). Partial eta-squared (η²) indicated large effects for health behaviors, WC, FPG, SBP, DBP, TC, and HDL cholesterol; non-HDL cholesterol showed a medium effect. TC and HDL cholesterol showed no significant change after completing the program. Conclusion: The SEE program improved health behaviors and clinical outcomes, supporting its integration into standard MetS care in nursing practice. Through e-health, education, exercise guidance, role modeling, and support, the program can boost confidence in adopting healthier behaviors and reduce CVD risk. Future studies should explore extending the program duration, as the 12-week period may have been insufficient to observe significant changes. Trial Registry Number: Thai Clinical Trials Registry (TCTR20250218014)